As Fontes no Jornalismo Radiofônico em Ambiente de Convergência - LOPEZ, Débora Cristina (Contemporanea : Revista de Comunicação e Cultura, 2009)
This article will discuss one of the central changes in the journalist routines in the convergence and technology context: their relationship with sources of information. For this reason, we take up the concept of source and its application to radio journalism, and, through examples, we place this discussion in a broader discussion: the use of technological tools in radio language. We do here a theorical review and a initial approach between convergence studies and radio journalism. The discussions are focused in authors from journalism theory, radio journalism and communication studies and convergence.